A Comprehensive Spectroscopic Analysis of the Ibuprofen Binding with Human Serum Albumin, Part I - Anna Ploch-Jankowska; Danuta Pentak (MDPI AG, 2020)
Human serum albumin (HSA) plays a fundamental role in the human body. It takes part in the transport of exogenic and endogenic substances, especially drugs. Ibuprofen (IBU) is one of the most commonly used non-steroidal anti-inflammatory drugs, used for pain relief, fever relief, and for anti-inflammatory purposes. The binding of ligands with HSA is a significant factor which determines the toxicity and the therapeutic dosages of these substances. The aim of this study was to compare the degree of ibuprofen binding with human serum albumin at various temperatures and protein solution pH values. In order to evaluate conformational changes in HSA caused by interaction with ibuprofen, spectrophotometric (first and second derivatives of the UV-VIS spectrum), and spectrofluorometric analyses were performed concerning the mutual interactions of IBU-HSA. The use of fluorescent spectroscopy allowed for recording fluorescent emissive spectra of HSA (5 × 10−6 mol/dm3) without and with the presence of ibuprofen (1 × 10−5-1 × 10−4 mol/dm3) at temperatures of 308, 310, 312, and 314 K at pH values of 6.5, 6.8, 7.4, 7.8, and 8.1. System fluorescence was excited by radiation of wavelengths of λex = 275 nm and λex = 295 nm. Based on this, original and modified Stern-Volmer, Scatchard, Klotz and Hill curves were determined. The data that were obtained showed a significant effect of temperature and pH of the human serum albumin solution on the strength and type of interaction of ibuprofen with HSA.